Transformasi Pendidikan Jasmani untuk Masa Depan yang Lebih Sehat - Arisandi, A. Resky; Faisal, Muh.; Saputra, Erlin (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2022)
Physical education faces significant challenges in the digital era and post-COVID-19 pandemic, where sedentary lifestyles are increasingly concerning and the health of the younger generation is a major concern. This study aims to analyze the transformations needed in physical education to create a healthier future for students. The research methodology uses a qualitative approach with a comprehensive literature review of 45 published scientific articles from 2020-2024, an analysis of physical education policies in Indonesia, and a review of physical education best practices in various countries. The results indicate that the transformation of physical education requires the integration of digital technology, a more holistic learning approach, the development of health literacy, and adaptation to the needs of the digital native generation. Key findings indicate the need for a paradigm shift from learning focused solely on motor skills to comprehensive health education encompassing physical, mental, and social aspects. This transformation involves the use of fitness apps, gamification of learning, project-based health learning, and the integration of mindfulness concepts into physical activity. The study's conclusions emphasize that future physical education must be adaptive, inclusive, and technology-based while maintaining the essence of physical activity as a foundation for health. Implementing this transformation requires strong policy support, ongoing teacher training, and multi-stakeholder collaboration between schools, families, and communities.